Painless Evidence-Based Medicine - Dans, Antonio L; Dans, Leonila F; Silvestre, Maria Asuncion A (John Wiley & Sons, Incorporated, 2017)
This updated edition of Painless Evidence-Based Medicine presents basic concepts and application of research statistics in simple and practical manner creating an introductory approach to the complex and technical subject of evidence-based medicine from experienced teachers. A simplified introductory approach to the complex and technical subject of evidence-based medicine from experienced teachers  Approaches learning from the vantage point of clinical questions on therapy, diagnosis, prognosis or harm rather than the framework of study designs Provides tables and boxed case studies throughout highlighting key topics, or difficult issues, in an easy to read manner Emphasizes applicability of EBM, encouraging readers to dissect the evidence and how results can be applied to individual patients with different circumstances, varying values and preferences New to the Second Edition are chapters on health screening, clinical practice guidelines, and major updates incorporating recommended trial criteria